2020
DOI: 10.1109/access.2019.2962869
|View full text |Cite
|
Sign up to set email alerts
|

3D Geometric Engineering of the Double Wedge-Like Electrodes for Filament-Type RRAM Device Performance Improvement

Abstract: The resistive switching variability and reliability degradation are the two major challenges that hinder the high-volume production of the Resistive Random Access Memory (RRAM) devices. In this work, a 3D electrode structure engineering method is proposed. The geometric parameters defined as electrode angle (EA), electrodes spacing (ES) and electrode trench depth (ETD) associated with the double wedge-like electrodes of the filament-type RRAM devices are studied for the first time. Our experimental results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Previous works have shown that the resistive switching mechanism of RRAM is related to the electrode material, [ 16,17 ] resistive switching oxide [, 18 ] and also device geometrical structure. [ 19,20 ] Extensive research has been carried out on the resistive switching mechanism of filamentary RRAM, the first discovered [ 21 ] as well as the most prevalent RRAM device. [ 22 ] In general, the resistive switching of filamentary RRAM originates from the repeated formation and rupture of conductive filament.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have shown that the resistive switching mechanism of RRAM is related to the electrode material, [ 16,17 ] resistive switching oxide [, 18 ] and also device geometrical structure. [ 19,20 ] Extensive research has been carried out on the resistive switching mechanism of filamentary RRAM, the first discovered [ 21 ] as well as the most prevalent RRAM device. [ 22 ] In general, the resistive switching of filamentary RRAM originates from the repeated formation and rupture of conductive filament.…”
Section: Introductionmentioning
confidence: 99%